A expressão da modalidade deôntica em língua espanhola - Prata, Nadja Paulino Pessoa (2013)
This study tries to identify the expression of deontic modality in the Spanish language widespread within texts extracted from internet. Based on a functionalist view of modality with the understanding that communication depends partly on the real speaker’s intentions in relation to what is expected to be shared by the hearer a search of the formal marks of a linguistic category was developed. In this concern two types of genres (opinion articles and editorial) and the values such as obligation, permission and prohibition were considered. Thus, deontic modality was observed by means of auxiliaries (poder, deber, haber, tener que) adjectives in predicative position, lexical verbs and nouns. As to the analysis it was necessary to observe and describe the discursive marks that generate the values of obligation, permission and prohibition keeping in mind the two genres that composed the corpus of this investigation in order to (i) generate possible questions about the category, (ii) to get knowledge about these markers in genres, (iii) to know how to identify them. This way the research is linked to a strand of description and linguistic analysis.